2002
DOI: 10.1159/000048227
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Vasopressin and Angiotensin II Receptors in the Thalamus and Brainstem of Inbred Polydipsic Mice

Abstract: Vasopressin (AVP), angiotensin II (Ang II) and oxytocin (OT) receptors were mapped in the brain of inbred polydipsic mice of the STR/N strain by quantitative in vitro autoradiography and receptor binding levels, compared with those found in control non-polydipsic mice of the ICR strain. A remarkable difference was evidenced in the thalamic paraventricular nucleus where AVP receptor binding was 7- to 10-fold higher in polydipsic mice than in control mice. Another disparity was observed in the hypothalamic parav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…We would note that the vast majority of the anatomical literature is from rat, while our pharmacological experiments were performed in mice. Although two studies have systematically compared OTR and V1AR distribution in mouse CNS, one of them focused on forebrain structures (Insel et al, 1991) while the other examined spinal distribution only as caudally as the trigeminal nucleus caudalis (Tribollet et al, 2002). One putative explanation for the V1AR-dependency of OXT-induced analgesia would be a species difference in receptor distribution.…”
Section: Discussionmentioning
confidence: 99%
“…We would note that the vast majority of the anatomical literature is from rat, while our pharmacological experiments were performed in mice. Although two studies have systematically compared OTR and V1AR distribution in mouse CNS, one of them focused on forebrain structures (Insel et al, 1991) while the other examined spinal distribution only as caudally as the trigeminal nucleus caudalis (Tribollet et al, 2002). One putative explanation for the V1AR-dependency of OXT-induced analgesia would be a species difference in receptor distribution.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests potential strain specific sex differences in V1aR in mice, i.e. a sex differences in the mammillary nucleus was found in C57B6 mice (Dubois Dauphin et al, 1996), but not in ICR mice (Tribollet et al, 2002). Although a thorough comparative analysis of the V1aR throughout the brain of commonly used laboratory mice is lacking, findings thus far suggests that mice, in general, may show few sex differences in V1aR binding density in the brain.…”
Section: Sex Differences In Vasopressin and Oxytocin Receptors In mentioning
confidence: 93%
“…For example, female prairie and montane voles showed higher OTR binding densities in the medial prefrontal cortex compared to males (Smeltzer et al, 2006), while male mandarin voles showed higher OTR mRNA expression in the MeA (Cao et al, 2013). It was also found that male ICR mice had lower OTR binding in the VMH than female ICR mice (Tribollet et al, 2002). Male S. xerampelinus singing mice had higher OTR binding in the MeA and hippocampal CA1 compared to females (Campbell et al, 2009).…”
Section: Sex Differences In Vasopressin and Oxytocin Receptors In mentioning
confidence: 95%
See 1 more Smart Citation
“…Investigation of polydipsia stemming from diabetes insipidus in humans indicates that dysregulation or mutation of the type-2 vasopressin receptor is a common cause (Moeller et al, 2013). Consistent with this notion, the STR/N inbred mouse strain, which exhibits a spontaneous water polydipsia, had 7- to 10-fold greater arginine vasopressin (AVP) binding in the thalamic paraventricular nucleus, and binding was absent in the hypothalamic paraventricular nucleus when compared to non-polydipsic control mice (Tribollet et al, 2002). Taken in conjunction with recent work demonstrating the role of AVP and type 1B receptors in the modulation of HPA axis function and the transition from excessive ethanol intake to dependence in rats (Edwards, Guerrero, Ghomeim, Roberts, & Koob, 2012), the potential role of AVP signaling in ethanol SIP deserves further attention.…”
Section: Steps Toward Enhancing the Utility Of Sip In The Study Omentioning
confidence: 77%